Representasi Simbolik sebagai Mekanisme Sosial: Studi tentang Hegemoni dan Pembentukan Karakter dalam Tradisi Bugis - Meisar Ashari; Eko Haryanto; Muhammad Ibnan Syarif; Eko Sugiarto (Society, 2025)
This study aims to uncover the symbolic meaning of Kawali, a traditional Bugis weapon, as a social mechanism and instrument for character formation in the South Sulawesi cultural system. Using a qualitative-ethnographic approach, this study was conducted over 9 months in the Bone and Luwu Regencies, involving 15 informants. Data were collected through observation, interviews, and documentation studies of lontara manuscripts and ritual practices. Then, they were analyzed thematically using Antonio Gramsci's cultural hegemony theory framework and Clifford Geertz's symbolic anthropology. The results show that Kawali is not merely a physical artefact but also a social symbol rich in traditional values, norms, and the Bugis' philosophy of life. Through pamor motifs, colors, and inheritance rituals, Kawali functions as a medium for communicating the values of siri’ (honor), pangaderreng (customary ethics), social responsibility, and loyalty to tradition. The symbolism of Kawali shows how Bugis cultural hegemony is exercised through moral consensus and aesthetic practices, rather than through coercion. In a modern context, Kawali is also reinterpreted as a symbol of identity and resistance to cultural homogenization. These findings confirm that traditional Kawali artifacts have contemporary relevance in character education, cultural preservation, and the formation of national identity. As living symbols, Kawali unites art, faith, and ethics in a single, evolving system of meaning.